Leading across cultures effective ministry and mission in the global church - Plueddemann, Jim. (Downers Grove, Ill. : IVP Academic, 2009)
The worldwide church is more interconnected than ever before, with missionaries going from everywhere to everywhere. Africans work with Australians in India. Koreans plant churches in London and Los Angeles. But globalization also creates challenges for crosscultural tension and misunderstandings, as different cultures have conflicting assumptions about leadership values and styles. Missiologist James E. Plueddemann presents a roadmap for crosscultural leadership development in the global church. With keen understanding of current research on cultural dynamics, he integrates theology with leadership theory to apply biblical insights to practical issues in world mission. Savvy discernment of diverse cultural underpinnings allows multicultural teams to work together with mutual respect for more effective ministry. The author shows how leaders can grow from an individualistic egocentric practice of leadership to a more global-centric approach. The future of the global church depends on effective multicultural leadership. God has called people from various contexts to minister and lead in every land for the sake of the gospel. Whether you are teaching English in China, directing information technology in Africa or pastoring a multiethnic church in North America, discover how you can better work and lead across cultures. - Publisher.
Multicultural leadership in the worldwide church. Leadership for a new day in world missions ; My pilgrimage in leadership ; Why crosscultural leadership? -- Leadership and culture. Leadership, cultural values, and the Bible ; Leadership and context ; Leadership and power ; Leadership and individualism Leadership and ambiguity -- Contextualizing leadership. A theology of leadership ; A theory of leadership -- Global leadership in practice. Developing vision and strategy ; Developing global leaders -- Epilogue : leadership in the global church.
Includes bibliographical references (p. [217]-228) and index.
Description based on print version record.
Keywords: Christian leadership; Multiculturalism -- Religious aspects -- Christianity; RELIGION / Christian Ministry / Pastoral Resources; Electronic books